The challenges of educating through Zoom in a pandemic context: investigating the experiences and perspectives of Portuguese teachers (Práxis Educativa, 2020)
With the Covid-19 pandemic, distance education was the main way to maintain teaching continuity. However, this rapid and unforeseen emigration to virtual environments revealed a set of adaptation challenges that question the preparation of schools to adhere to this teaching modality. Focusing on the perspectives of Portuguese teachers about their online teaching experiences, this article explores the challenges experienced by these professionals. Methodologically, it is supported by the realization of 5 focus groups online via Zoom (N = 32). As a result, it was identified 4 types of challenges: communication (digital monologues and psychological exhaustion), pedagogical (lack of skills, evaluation/overload of work and the impossibility of practical classes), social (incompatibilities with personal life and conflict management) and technological (lack of resources and technophobia).Keywords: Distance education. E-learning. Covid-19.